Development of pulverized biomass combustion for industrial boiler: A study on bluff body effect - Niwat Suksam; Jarruwat Charoensuk (My University, 2019)
Experimental and numerical investigations were performed for pure pulverized biomass combustion in a 300 kW laboratory swirl burner with a pre-combustion chamber. This work investigated a bluff body at the burner tip and how that affected the combustion characteristics in comparison with a conventional annular orifice burner. The combustion performances were assessed by measuring the temperature distribution in a pre-combustion chamber and furnace, oxygen concentration, and emissions (CO and NOx). Simulations were carried out and validated, providing insight on flow aerodynamics, particle trajectories, species concentrations, and temperature in a pre-combustion chamber and furnace. It was concluded that the bluff body provided a superior performance in terms of flame attachment and combustion efficiency. However, the emissions were high due to the contribution of thermal NOx.
Keywords: Bluff; Thermochemical Biomass Conversion Processes